2010
DOI: 10.2486/indhealth.ms1055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxicity in Petrol Station Workers in South India Using Micronucleus Assay

Abstract: In this study, the micronucleus (MN) frequency was assessed as a measure of genotoxicity in exfoliated cells of buccal mucosa extracted from 110 petrol pump workers and 100 controls. For each individual, 3,000 exfoliated buccal cells were analyzed. The individuals used in the study were grouped based on their smoking, drinking alcoholic beverages, and tobacco chewing habits. There was a significantly higher frequency of micronucleated cells in the exposed workers to petrol than in the unexposed control populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
2
13
1
1
Order By: Relevance
“…Studies have used research of nuclear anomalies in buccal mucosal cells to investigate the genotoxicity of occupational and environmental exposure to fossil fuel products [12,13,71,72]. The MN results of this study were not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies have used research of nuclear anomalies in buccal mucosal cells to investigate the genotoxicity of occupational and environmental exposure to fossil fuel products [12,13,71,72]. The MN results of this study were not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…A study on those exposed to petrol has shown increased frequencies of micronuclei in buccal mucosal cells, which were linked to high risk for cancer as a long-term effect needing careful monitoring. 36 Biomarkers such as pyknotic cells, nuclear bud, karyolytic cells, karyorrhectic cells, etc , found in BMCyt have been associated with genetic defects in genome maintenance, exposure to genotoxic agents, accelerated ageing, risk of oral cancer, and neurodegenerative diseases. 37…”
Section: Discussionmentioning
confidence: 99%
“…The volatile nature of petrol makes it readily available in the atmosphere at any time it is dispensed, especially at petrol filling stations (1) . Benzene (C6H6) is a volatile organic compound (VOC) with a very stable ring-shaped chemical structure that constitutes the base of the aromatic hydrocarbon family.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of benzene and its reactive metabolites leads to continuous production of reactive oxygen species (ROS), which damages DNA, RNA, and proteins by chemical reactions such as oxidation, nitration, and halogenations leading to genetic modification and alterations in the functions of important enzymes and proteins (6) . Thus, this study aims to promote health of petrol stations' workers occupationally exposed to benzene in their daily work with objectives to (1) Assess trans,trans-muconic acid (ttMA) level in urine as a biological marker for benzene exposure (2) Estimate the extent of oxidative stress by measuring the Malondialdehyde (MDA) level in P blood (3) Assess the activity of erythrocytes superoxide dismutase (SOD) enzyme (4) Identify the personal and occupational factors that may be associated with level of Malondialdehyde (MDA) detected, activity of superoxide dismutase (SOD) enzyme and level of trans,trans-muconic acid (ttMA) in studied groups.…”
Section: Introductionmentioning
confidence: 99%